Polish pupils from the Alpha generation and their lifestyle - Piepiora, Paweł; Brojanowska, Astrid; Vveinhardt, Jolita (Journal of Education, Health and Sport, 2025)
The present study explores the emerging interest in the phenomenon of the Alpha generation, a subject on which there is a paucity of both theoretical and empirical works. To date, there has been no organised attempt to synthesise the extant knowledge on the lifestyles of today’s youngest generation of students from different countries worldwide. The present paper thus aims to address this knowledge gap by presenting a concise overview of the lifestyles of Polish students of the Alpha generation. The paper addresses the main factors shaping health in this age group by referring to diet and eating habits, mental health, physical activity, and sleeping, with particular attention given to problems resulting from excessive use of digital media and minimising physical activity. It was concluded that, in Polish schools, for the sustainable development of students of the Alpha generation, there is a need to introduce health education and close intersectoral cooperation.